The Silencing Effect of microRNA miR-17 on p21 Maintains the Neural Progenitor Pool in the Developing Cerebral Cortex - Chen, Yase; Bian, Shan; Zhang, Jing; Zhang, Haijun; Tang, Beisha; Sun, Tao (Frontiers in Neurology, 2014)
Expansion of the neural progenitor pool in the developing cerebral cortex is crucial for controlling brain size, since proliferation defects have been associated with the pathogenesis of microcephaly in humans. Cell cycle regulators play important roles in proliferation of neural progenitors. Here we show that the cyclin-dependent kinase inhibitor p21 (also called Cdkn1a and Cip1) negatively regulates proliferation of radial glial cells (RGCs) and intermediate progenitors (IPs) in the embryonic mouse cortex. MicroRNA-17 (miR-17) displays reciprocal expressions with p21 in the developing cortex. Opposite to p21, miR-17 promotes expansion of RGCs and IPs, as demonstrated by overexpressing miR-17 precursors and miR-17 sponges that can knock down the endogenous miR-17. Moreover, p21 is a putative target normally silenced by miR-17. Co-expression of miR-17 with p21 is sufficient to rescue the negative regulation of p21 on progenitor proliferation. Our results indicate a mechanism of controlling the neural progenitor pool, which is to suppress p21 by miR-17 in the developing cortex.